PT Kirana Permata's Crisis Communication Strategy Regarding Environmental Issues and Social Responsibility - Muhammad Rio Putra Pratama; Komaruddin; M. Arif Setiawan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the crisis communication strategy implemented by PT Kirana Permata in dealing with environmental issues and social responsibility and identify supporting and inhibiting factors that affect its implementation. This study uses a qualitative method with a descriptive approach, with data obtained through interviews, observations, and documentation involving the company and the surrounding community. The research analysis uses the Situational Crisis Communication Theory (SCCT) proposed by W. Timothy Coombs to understand the company's response in facing a crisis and maintain its reputation in the eyes of the public. The results of the study show that PT Kirana Permata implements a crisis communication strategy through an open and responsive approach, two-way communication through interactive dialogue, informative and persuasive information delivery, and good internal coordination in handling evolving issues. The supporting factors for the strategy include company management support, inter-division cooperation, and good communication relations with the community, while the inhibiting factors include the difficulty of gathering the community at the same time, differences in public perception of environmental issues, and limitations in the dissemination of information. This study concludes that the crisis communication strategy implemented by PT Kirana Permata is able to help the company maintain harmonious relations with the community and manage environmental issues and social responsibility more effectively through open, dialogical, and sustainable communication.